Plan de mercadeo del dulce de leche en el taller de procesos lácteos de la ESPAM MFL - Moncayo Torres, María Victoria (2013)
The present study aimed to develop a marketing plan for sweetened milk of the ESPAM MFL and display the results of the proposal, in order to solve the problem in the Dairy Workshop in the institution. The work was developed in four stages, aiming new markets to expand production and marketing of the product. We applied methods and tools needed for this type of research, the execution of market research reveal the preferences of buyers who are part of the population of the Canton; additionally surveyed managers or owners at 6 sales point of the locality, the coordinator of Dairy Process workshop was interviewed, we did an observation and designed a SWOT matrix that facilitated the diagnosis of internal and external factors of the workshop; advertising strategies were designed too: brand, packaging, flyers, brochures, TV ads, radio and internet distribution channels from suppliers of raw materials to the delivery of final product to consumers, ending with the structure of a formal marketing plan which was socialize to the ESPAM workshop staff, where it was concluded that the marketing plan is ideal for product sales and gaining position in the market.